Molecular diversity of Paenibacillus larvae strains isolated from Lithuanian apiaries - Amšiejute, Paulina; Jurgelevičius, Vaclovas; Mačiulskis, Petras; Butrimaite-Ambrozevičiene, Ceslova; Pilevičiene, Simona; Janeliunas, Zygimantas; Kutyriova, Tatjana; Jacevičiene, Ingrida; Paulauskas, Algimantas (Frontiers in Veterinary Science, 2022)
Paenibacillus larvae bacterium is known to be the causative agent of American foulbrood (AFB), a widespread, highly contagious and fatal disease in honey bees (Apis mellifera). There are four strains of Paenibacillus larvae that are named after their enterobacterial repetitive consensus (ERIC), and a fifth ERIC genotype has recently been found. ERIC I and ERIC II genotypes have spread worldwide and are considered the most important because of their high virulence. In this study, a total of 108 independent P. larvae isolates from different geographical regions in Lithuania collected between 2011 and 2021 were investigated for the first time for their genetic diversity using multiple-locus variable number of tandem-repeat analysis (MLVA). The aims of this study were to detect which enterobacterial repetitive intergenic consensus (ERIC) genotype is the most common in Lithuania apiaries, identify and differentiate subtypes of the defined genotype, and analyse how bacterial molecular diversity has changed and spread over time in different parts of Lithuania. Molecular analysis data showed that 100 % of P. larvae bacterial isolates from Lithuania were the ERIC I genotype, and the results of capillary electrophoresis allowed nine P. larvae strain subtypes to be identified using the MLVA method.